Menalar Khayal: Reasoning the Imagination - Herawan, Michael Binuko Sri (Telkom University, 2023)
“Menalar Khayal” (Reasoning the Imaginaton) is an art project that tried to elaborate between fcton (imagining) and scientfc (reasoning) processes to create a series of artworks that illustrates a fcttous study about a creature named Megaptera novalevitae, a fctonal fying whale. The process of reasoning the imaginaton was a back-and-forth process and afected the creaton of the artworks. The artwork confguraton in this project tried to illustrate an idea about this fctonal creature. Then, it combined it with visuals that remind us of the illustratons from science or school textbooks. This approach was made to absorb audiences into the fctonal whale and develop their imaginaton and story about the creature. Using this approach, I also aim to create diferent kinds of storytelling using artworks. The visual presentaton in this project tried to bring audiences’ imaginaton to the illustratons or study propertes when technology was not so advanced and relied on people’s adept skills to illustrate and record their fndings. Therefore, this project used conventonal mediums: drawings, prints, and sculpture. This project departs from my imaginaton, partcularly having an interest in studies and observatons of the feld of science, especially biology and paleontology. In this project, the imaginaton is the main engine of the creaton process, as it needs to be equipped to read the works.